Generation of Reduced Nicotinamide Adenine Dinucleotide for Nitrate Reduction in Green Leaves - Klepper, Lowell (1971)
An in vivo assay of nitrate reductase activity was developed by vacuum infiltration of leaf discs or sections with a solution of 0.2 m KNO(3) (with or without phosphate buffer, pH 7.5) and incubation of the infiltrated tissue and medium under essentially anaerobic conditions in the dark. Nitrite production, for computing enzyme activity, was determined on aliquots of the incubation media, removed at intervals. By adding, separately, various metabolites of the glycolytic, pentose phosphate, and citric acid pathways to the infiltrating media, it was possible to use the in vivo assay to determine the prime source of reduced nicotinamide adenine dinucleotide (NADH) required by the cytoplasmically located NADH-specific nitrate reductase. It was concluded that sugars that migrate from the chloroplast to the cytoplasm were the prime source of energy and that the oxidation of glyceraldehyde 3-phosphate was ultimately the in vivo source of NADH for nitrate reduction. This conclusion was supported by experiments that included: inhibition studies with iodoacetate; in vitro studies that established the presence and functionality of the requisite enzymes; and studies showing the effect of light (photosynthate) and exogenous carbohydrate on loss of endogenous nitrate from plant tissue. The level of nitrate reductase activity obtained with the in vitro assay is higher (2.5- to 20-fold) than with the in vivo assay for most plant species. The work done to date would indicate that the in vivo assays are proportional to the in vitro assays with respect to ranking genotypes for nitrate-reducing potential of a given species. The in vivo assay is especially useful in studying nitrate assimilation in species like giant ragweed from which only traces of active nitrate reductase can be extracted.